Acute Effects of Muay Thai on Blood Pressure and Heart Rate in Adolescents with Overweight/Obesity - Saraiva, Bruna Thamyres Ciccotti [UNESP]; Prado, Wagner Luiz do; Vanderlei, Luiz Carlos Marques [UNESP]; Milanez, Vinícius Flávio; Damato, Tatiana Machado de Mattos [UNESP]; Santos, Amanda Barbosa dos [UNESP]; Tebar, William Rodrigues; Christofaro, Diego Giulliano Destro [UNESP] (MDPI, 2022)
Background: To analyze the effects of a single session of Muay Thai (MT) on blood pressure and heart rate in adolescents with overweight/obesity. Methods: A total of 27 adolescents with overweight/obesity (12.85 ± 2.08 years), 13 girls and 14 boys, performed 60 min of MT composed of general and modality-specific exercises, as well as combat at the end. Anthropometric measurements were taken and body fat (BF) was measured using DEXA. Excess weight was attested via the body mass index (BMI) and BF. Systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were measured by an oscillometric device before, immediately after MT, and 10, 20 and 30 min of recovery. Results: SBP decreased in boys after 20 min (d = −0.73) and 30 min (d = −0.78) of recovery, and in girls after 20 min (d = −0.56). DBP decreased in girls immediately after the session (d = −0.90) and after 10 min (d = −1.00); for the total sample, when analyzed across sex, DBP decreased immediately after the session (d = −0.70) and after 10 min (d = −0.52). No effect of MT on HR recovery was observed. Conclusions: A single MT session induces positive changes in blood pressure, with a greater impact on SBP in girls.
Keywords: blood pressure; exercise; heart rate; martial arts; obesity